Cuidando do presente e desejando o tempo futuro: comunicação entre família, profissionais de saúde e criança e adolescente com câncer - Borges, Amanda Aparecida (2020)
The news of juvenile childhood cancer generates, for the family, a break in expectations and a feeling of unpreparedness in the face of the unknown. Thus, what often occurs is a process of adapting the entire family system to this new reality, seeking an interaction with the individuals involved in the process of treating children / adolescents with cancer. In this context, this research aimed to understand the communication experience established between child / adolescent, health professionals and family in the face of the child's illness. This is a study with a qualitative approach, which adopted Symbolic Interactionism as its theoretical framework and the Grounded Theory as its Methodological Framework. Eleven families and child / adolescent undergoing chemotherapy for cancer participated in this study, totaling 26 participants. Regarding health professionals, 13 individuals from different professional categories participated. For data collection, participant observation was used, where the researcher observed the existing conversation between the actors involved in the treatment of the child / adolescent. Based on this observation, a posteriori, semi-structured interviews were carried out with the participants and the data analysis was carried out concurrently with the collection, according to the steps recommended by the referential. It was possible to understand the experience of individuals in three Phenomena: “Seeking tirelessly for answers”; “Feeling desolate for having a changed life path” and “Communicating the importance of treatment time”. The first points out the need of the family to know about the prognosis of the child / adolescent, the fear of losing it is at the heart of communication. The second is expressed by the child / adolescent's feeling of sadness in experiencing moments of deprivation, enhancing the search for understanding the reason for experiencing this situation. The last is the speech of health professionals to believe in treatment, after all, there is no other way for the child's rehabilitation. These phenomena pointed out the Central Category and the Theoretical Model: “Waiting to reach the future time”, which represents the communication experience of the actors involved in the process of treating children / adolescents with cancer, aiming at the need for care and to live the therapy to glimpse the cure of the disease. The results lead to a reflection on the role of health professionals in communicating with children / adolescents and family, since they want to know beyond the side effects and the procedures that are being performed, they want to talk about a time that has not yet come, but that is intrinsic to your experience. Through the emerging theoretical model, it is possible to list several strategies to be used by health professionals to assist them in communicating with family, children and adolescents in order to facilitate the interaction between the actors.